Pengaruh Kepatuhan Pembayaran Wajib Pajak Terhadap Pendapatan Asli Daerah (PAD) Kabupaten Sampang - Syaroni; Christine Cicilia Sinaga; Ahmad Zaki; Mohammad Fauzan Al Angsyari; Fellysita Angelina; Muhammad Naufal Firzatulloh Jatmiko; Revienda Anita Fitrie; Melda Fadiyah Hidayat (Al-Zayn : Jurnal Ilmu Sosial & Hukum, 2026)
Local revenue (PAD) is an important measure for assessing a region’s financial self-reliance, but its contribution in Sampang Regency remains low and has not yet become the primary source of local revenue. This indicates challenges in optimizing local tax revenue, particularly regarding the level of taxpayer compliance. This study aims to examine how taxpayer compliance can improve PAD. The method used is a qualitative approach with a literature review, involving data collection from scientific journals, books, and relevant documents. Data analysis was conducted by qualitatively describing, reviewing, comparing, and interpreting previous research findings to identify patterns of relationships between variables. The results indicate that taxpayer compliance has a positive impact on local tax revenue and PAD. Several factors influencing compliance include tax knowledge, economic conditions, service quality, tax penalties, and public awareness campaigns. The low contribution of local taxes to PAD indicates that the level of taxpayer compliance is still not optimal. Therefore, improving compliance through education, service improvements, and the enforcement of penalties is a critical strategy to support local financial autonomy.